Discovering statistics using R. - Field, Andy; Miles, Jeremy; Field, Zoë (SAGE Publications Ltd, 2012)
"An entertaining and foundational manual on how to use R to solve statistical problems. Discovering Statistics Using R uses an irreverent and innovative approach to explain how students can use R to approach statistical problems. It introduces readers to the software environment of R and shows how it can be used in the field of statistics. The authors understand that using R and concepts of statistics can be difficult to access and so use humour and extremely informal and conversational language to ease comprehension. It uses multiple engaging examples as well as easy problems to ensure that the concepts of the software as well as the statistical concepts can be easily digested by the readers. Given this book's accessibility, fun spirit, and use of bizarre real-world research it should be essential for anyone wanting to learn about statistics using the freely-available R software. KEY FEATURES: Detailed introduction to the software environment of R guides the reader through how to use it. Relates theory to the real world to help students think about how the software can be applied to real research problems Humorous and accessible language that simplify complex concepts and processes Numerous problems and examples that test the readers understanding of the subject"--